Paradigm shifts in northern art, community and environment studies for art teacher education. Issue 1 (2021) - Huhmarniemi, Maria; Jokela, Timo; Hiltunen, Mirja
Abstract: In Northern Finland, where this study takes place, nature is a typical setting for recreational activities and employment. At the University of Lapland, attention has been given to art teacher education that supports the continuation of the Northern ecoculture and enhances human–nature connectedness. In this article, we discuss art, community and environmental (ACE) studies developed through international collaborations and joint, long-term action research based on the arts. These studies are part of art teacher training and an international master's degree programme in Arctic art and design. This article explains the paradigm changes that have impacted the aims and methods employed in ACE studies since the 1990s. The discussion is framed by a Western theoretical shift from environmental aesthetics to new materialism, post-humanism and decolonisation. We conclude that ACE projects can enhance revitalisation and increase capacities to retain cultural pride and local ecocultures. Art education that is carried out in a place-specific manner, in cooperation with local communities, is one way to keep traditions alive and foster environmentalism in the North. The article has international relevance for developing art teacher training in Arctic communities but also in other remote locations in which strong bonds between nature and culture are maintained. Highlights: Art-based environmental education in art teacher training has been implanted as environmental art and community art activities. Many artists and art researchers endorse a post humanistic relationship with the environment challenging methods for art education. Art education can help to release eco-anxiety and increase educators' capacities in facilitating transformative experiences. Art education in cooperation with local communities is one way to keep traditions alive and foster environmentalism in the North. Art-based action research is a research strategy to develop art teacher training and art education methods.